Matching PV Production and Electricity Load on Household Level at High-Latitude Locations - Jouttijärvi Sami; Karttunen Lauri; Ranta Samuli; Miettunen Kati (Germany, 2025)
T his study analyses the potential for the self-consumption of photovoltaic (PV) electricity for different detached houses and PV systems in Nordic conditions. The aim is to reduce the need for battery energy storage or balancing power generation by fossil fuels to mitigate the high diurnal and weather-dependent variation of PV production. Increasing self-consumption is crucial to increase the usability and economic value of PV electricity on households and to smoothen the grid integration of PV on local and national levels. Three differently oriented monofacial PV systems and one vertically mounted bifacial PV system are compared as clean electricity sources for different detached houses in a high-latitude location. The focus is on total energy production and the potential for selfconsumption. For monofacial systems, the self-consumption potential was dominated by the electricity load profile, and the differences in self-consumption between differently oriented systems were small, except when large, flexible loads allowed to utilize high amount of PV electricity at the spot. For vertical bifacial system, the highest overall production and convenient power production profile allowed superior self-consumption compared with monofacial PV systems.
Proceedings of the 40th European Photovoltaic Solar Energy Conference and Exhibition in Lisbon, Portugal